The Influence of The Internal Control System And Accountability On Fraud Prevention In Village Financial Management - Pattawe, Abdul (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to examine and analyze the influence of village internal control systems and accountability on fraud prevention in village financial management both simultaneously and partially. This type of research is survey research with quantitative methods and uses primary data. The population in this study is the village in Sigi Biromaru District, Sigi Regency. The sampling technique used in this study was purposive sampling, with 6 respondents in each village, namely 60 respondents. The analysis technique used warpPLS7.0 The results of this study indicate that internal control system has a partially positive effect and significant on fraud prevention in village financial management, and accountability has a partially positive effect and significant on fraud prevention in village financial management.